2019
DOI: 10.1080/00071668.2019.1673318
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase and xylo- oligosaccharide prebiotic improve the growth performance and concentration of potentially prebiotic oligosaccharides in the ileum of broiler chickens

Abstract: 1. The objective of this study was to investigate the effect of supplementing broiler diets with xylanase or xylo-oligosaccharide (XOS) on growth performance, the concentration of non-starch polysaccharide (NSP) hydrolysis products in the ileum and concentration of short chain fatty acids (SCFA) in the caeca of broiler chickens. 2. In total, 500 male Ross 308 broilers were used in this 29-day (d) study. The treatments were organised into a 2 × 2 plus 1 factorial arrangement consisting of two additives (xylanas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 42 publications
2
41
1
Order By: Relevance
“…In the present study, although there were no changes in performance, xylanase improved BW homogeneity, which is intriguing, given the digestibility data. Likewise, predicting long-term effects of a diet on performance parameters, such as BW gain or FCR, based on nutrient digestibility responses to xylanase also appeared to be incongruous in previous studies [ 49 ]. However, when estimating the total intake of digestible nutrients, using digestibility coefficients, the low digestibility associated with the xylanase supplementation disappears, showing a better adjusted estimation on digestibility effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, although there were no changes in performance, xylanase improved BW homogeneity, which is intriguing, given the digestibility data. Likewise, predicting long-term effects of a diet on performance parameters, such as BW gain or FCR, based on nutrient digestibility responses to xylanase also appeared to be incongruous in previous studies [ 49 ]. However, when estimating the total intake of digestible nutrients, using digestibility coefficients, the low digestibility associated with the xylanase supplementation disappears, showing a better adjusted estimation on digestibility effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest a release of encapsulated nutrients or/and the production of XOS or AXOS from the plant cell walls, as suggested by some authors [ 46 , 47 , 48 ]. Thus, several studies have reported benefits when XOS were included in pig and poultry diets [ 49 , 50 , 51 , 52 ]. Therefore, the XOS obtained when xylanase was added could improve the relative abundance of Lachnospiraceae family, and several members of this family are recognized as butyric-producer bacteria [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, endo-xylanase, and exo-xylanase are the most important contributors to xylan depolymerization. Until now, vast applications of xylanase have been extensively explored based on its ability in xylan degradation, for example, biofuels production [6][7][8], pulp and paper bleaching [9][10][11], bioactive compounds [12][13][14], animal feed [15,16], and baking [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…8 The addition of xylo-oligosaccharides shows a significant difference in the growth performance of broilers. 9 The use of supplements, namely probiotics and prebiotics (synbiotics) improves the health and productivity of poultry. 10 Moringa oleifera is a potential medicinal plant that is used to enhance the immunity and intestinal health of broilers, as well as reduce the number of E.coli in the intestines.…”
Section: Introductionmentioning
confidence: 99%